Weight Loss Interventions for Hispanic Women in the United States: A Systematic Review. (20th August 2021) - Morrill, Kristin E.; Lopez-Pentecost, Melissa; Molina, Lupita; Pfander, Jeanne L.; Hingle, Melanie D.; Klimentidis, Yann C.; Thomson, Cynthia A.; Garcia, David O.
Abstract : Background . Obesity rates in Hispanic women residing in the United States (U.S.) are disproportionately high, increasing the risk of obesity-related disease and mortality. The effectiveness of interventions targeting weight loss in this population remains largely unknown. Purpose . The purpose of this review was to systematically evaluate the evidence related to the effectiveness of weight loss interventions conducted among U.S. Hispanic women and provide guidance for future research. Methods . Bibliographic databases ( n = 10, from each database's inception to July 2, 2019) were searched using the PRISMA guidelines for systematic reviews. Randomized controlled trials (RCTs) and quasi-experimental studies with weight change outcomes were included. Results were described in a narrative synthesis. Results . 5, 423 articles were assessed for eligibility based on inclusion criteria; 15 studies were included in the final review. Nine trials were RCTs and six were quasi-experimental studies; all but six were pilot studies. Most studies recruited overweight or obese women with no existing medical conditions and did not follow participants beyond the intervention. All trials were delivered in-person. Intervention strategies and content and weight change outcomes were highly variable. Conclusions . RCTs with statistically powered sample sizes are needed to robustly test the effects of weight loss interventions in this population.